Oral squamous carcinoma cells secrete RANKL directly supporting osteolytic bone loss - Zhang, Xiaoyi; Rossa Júnior, Carlos [UNESP]; Liu, Min; Li, Fei; D'Silva, Nisha J.; Kirkwood, Keith L. (Elsevier B.V., 2013)
Objective: Local invasion of bone is a frequent complication of oral squamous cell carcinoma (OSCC). Development of these osteolytic lesions is mediated by osteoclasts. Receptor activation of NF-kappa B ligand (RANKL) signaling, counteracted by osteoprotegerin (OPG), regulates osteoclastogenesis. Previous studies in rodent models have demonstrated that inhibition of RANKL decreases tumor growth and lesions within bone. However, the contributory role of OSCC cells to this disease process has yet to be defined.Methods: RANKL expression was assessed in a panel of OSCC cell lines by qPCR, flow cytometry, and ELISA. Induction of osteoclastogenesis was assessed by co-culture with macrophages or with OSCC-derived conditioned medium. In an animal model of bone invasion, nude mice were injected intratibially with UMSCC-11B cells expressing a RANKL luciferase promoter to detect tumor-derived RANKL activity. Osteolytic lesions were analyzed by X-ray, micro-CT, and histological methods. RANKL expression was assessed in human OSCC tissues by immunohistochemistry.Results: We demonstrated that OSCCs express varied levels of all RANKL isoforms, both membrane-bound and soluble RANKL. Both co-culture and treatment with OSCC-conditioned media induced osteoclastogenesis. In mice, we demonstrated human RANKL promoter activity during bone invasion. Over the course of the experiment, animals suffered osteolytic lesions as RANKL-driven luciferase expression increased with time. After 8 weeks, human-derived RANKL was detected in areas of bone resorption by immunohistochemistry. Similar epithelial RANKL expression was detected in human OSCC tissues.Conclusion: These data demonstrate the ability of OSCCs to produce RANKL, directly altering the tumor microenvironment to increase osteoclastogenesis and mediate local bone invasion. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: RANKL; Oral cancer; Osteoclastogenesis